Economia e filosofia - Stefano Zamagni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1994)
– The present essay addresses the question of whether or not economics can usefully progress without establishing a special link with philosophy. It aims to provide an overview for a broad audience of working economists and to suggest possibilities for research to those with specific interests in the foundations of economic discourse. After the introductory and motivational remarks of sections 1 and 2, section 3 deals with the crisis of the neopositivist research programme and its impact on economic epistemology. Section 4 presents the main reasons accounting for the recent revival of the political dimension in economic research. Section 5 is concerned with the moral relevance and presuppositions of economic processes and outcomes and addresses the problems faced in making value assertions a part of the critical discourse of economics. Few general considerations conclude the paper.
Keywords: 330